Parasocial Intimacy and Fan Culture with K-Pop Artists in Indonesian Digital Media: A Study of Fan-Idol Relationships on Social Media Platforms - Marsaa Salsabila Syawal (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
This research explores parasocial intimacy within Indonesian K-pop fandom, examining how digital media shapes fan-idol relationships. Using a qualitative approach and literature study method, this research investigates the mechanisms that underlie parasocial phenomena, fan culture and digital media. This research finds that the significant role of social media in providing fans with glimpses into their idols' personal and professional lives, enhancing socio-emotional connections. While existing recognizes the impact of cultural context on fan dynamics, emphasizing the need for future research to explore factors like gender, age, and social background. This study contributes to the global conversation on parasocial intimacy and fan-idol relationships in the digital age.